Cytotoxicity and Antiproliferative Activity Assay of Clove Mistletoe (Dendrophthoe pentandra (L.) Miq.) Leaves Extracts - Vida Elsyana; Maria Bintang; Bambang Pontjo Priosoeryanto (Advances in Pharmacological Sciences)
Clove mistletoe (Dendrophthoe pentandra (L.) Miq.) is a semiparasitic plant that belongs to Loranthaceae family. Clove mistletoe was traditionally used for cancer treatment in Indonesia. In the present study, we examined cytotoxicity of clove mistletoe leaves extracts against brine shrimps and conducted their antiproliferative activity on K562 (human chronic myelogenous leukemia) and MCM-B2 (canine benign mixed mammary) cancer cell lines in vitro. The tested samples were water extract, ethanol extract, ethanol fraction, ethyl acetate fraction, and n-hexane fraction. Cytotoxicity was screened using Brine Shrimp Lethality Test (BSLT). Antiproliferative activity was conducted using Trypan Blue Dye Method and cells were counted using haemocytometer. The results showed that n-hexane fraction exhibited significant cytotoxicity with LC50 value of 55.31 μg/mL. The n-hexane fraction was then considered for further examination. The n-hexane fraction of clove mistletoe could inhibit growth of K562 and MCM-B2 cancer cell lines in vitro. The inhibition activity of clove mistletoe n-hexane fraction at concentration of 125 μg/mL on K562 cancer cell lines was 38.69%, while on MCM-B2 it was 41.5%. Therefore, it was suggested that clove mistletoe had potential natural anticancer activity.